Vol. 9680 : Atmospheric and Ocean Optics: Atmospheric Physics: 21st International Symposium, 22–26 June 2015, Tomsk, Russian Federation; [proceedings]; Proceedings of SPIE - Matvienko G. G.; Romanovskii O. A. (2015, 2015)
Title screen